Functional roles of graft‐infiltrating lymphocytes during early‐phase post‐transplantation in mouse cardiac transplantation models. (14th November 2021) - Ganchiku, Yoshikazu; Goto, Ryoichi; Kanazawa, Ryo; Ota, Takuji; Shibuya, Kazuaki; Fukasaku, Yasutomo; Kobayashi, Nozomi; Igarashi, Rumi; Kawamura, Norio; Zaitsu, Masaaki; Watanabe, Masaaki; Taketomi, Akinobu
Summary: Immunological behavior of graft‐infiltrating lymphocytes (GILs) determines the graft fate (i.e., rejection or acceptance). Nevertheless, the functional alloreactivity and the phenotype of GILs at various times during the early post‐transplantation phase have not been fully elucidated. We examined the immunological activities of early‐phase GILs using a murine model of cardiac transplantation. GILs from 120‐h allografts, but not 72‐h allografts, showed robust activation and produced proinflammatory cytokines. In particular, a significant increase in CD69 + T‐bet + Nur77 + T cells was detected in 120‐h allografts. Furthermore, isolated GILs were used to reconstitute BALB/c Rag2 −/− γc −/− (BRG) mice. BRG mice reconstituted with 120‐h GILs displayed donor‐specific immune reactivity and rejected donor strain cardiac allografts; conversely, 72‐h GILs exhibited weak anti‐donor reactivity and did not reject allografts. These findings were confirmed by re‐transplantation of cardiac allografts into BRG mice at 72‐h post‐transplantation. Re‐transplanted allografts continued to function for >100 days, despite the presence of CD3 + GILs. In conclusion, the immunological behavior of GILs considerably differs over time during the early post‐transplantation phase. A better understanding of the functional role of early‐phase GILs may clarify the fate determination process in the graft‐site microenvironment. Abstract : Graft Infiltrating Lymphocytes (GILs) change their immunological behavior depending on time after transplantation. While 120 h GILs show very strong alloreactivity, 72 h GILs show very weak alloreactivity and do not reject allograft by themselves.